Construction and validation of a predictive model for postoperative stent occlusion in patients undergoing iliac vein stenting based on an explainable machine learning model - Jiang, Yan; Nie, Dan; Zhang, Lifeng; Tang, Xia; Li, Haolu; Li, Long; He, Huqiang; Liu, Yang; Mao, Weijian; Xiong, Zhiwei; Jin, Chengyong (Frontiers in Surgery, 2025)
ObjectiveThis study aims to develop an interpretable machine learning model for predicting post-operative iliac venous stent occlusion risk.MethodsEmploying a retrospective cohort design, data from 826 patients across seven hospitals (January 2017–June 2024) were incorporated with stratified sampling into training (n = 661) and test sets (n = 165), ensuring no significant baseline characteristic differences (all P > 0.05). An AutoML framework was constructed using the Improved Sequoia Optimization Algorithm (ISequoiaOA), integrated with LASSO feature selection and SHAP interpretability analysis; model evaluation incorporated six core metrics (including AUC/PR-AUC), calibration performance, and Decision Curve Analysis (DCA).ResultsIn independent testing-set validation, the AutoML model demonstrated superior robustness: ROC-AUC reached 0.9251 and PR-AUC 0.8712. Decision curve analysis confirmed significantly higher clinical net benefit across a wide threshold probability range (1%–87%) compared to conventional approaches, indicating exceptional generalizability. Calibration curves revealed the lowest Brier score (0.123) in the test set, further validating predictive accuracy. Outperforming comparative models [e.g., XGBoost [ROC-AUC 0.8203] and LightGBM [PR-AUC 0.7806]], AutoML dominated across all metrics including accuracy (0.7417) and F1-score (0.7559). Concurrently, SHAP analysis quantified critical feature contributions: Pathogenic triad (DVT + Cockett + PE); Hemodynamic thresholds (common femoral and external iliac vein recanalization rates both <70%); Stent geometric parameters (diameter >14 mm/inferior vena cava segment length >20 mm); With CRP > 10 mg/L and D-dimer > 1.5 mg/L coexistence elevating occlusion risk.ConclusionThe occlusion prediction system integrating AutoML with explainable AI successfully quantifies multi-level interactions, surpassing traditional predictive dimensions to provide evidence-based support for personalized anticoagulation and stent optimization.